Vacunación en adultos (2002)
¿Qué es una vacuna?/¿Cómo funciona una vacuna?/¿La vacunación es exclusiva de los niños?/Esquema de vacunación de aultos normales/Difteria y tetanos/Rubeóla, sarampion y paperas/Hepatiris A/Hepatitis B/Influenza/Varicela/Neumococo/Fiebre amarilla/Malaria/VIH-SIDA